Preparatory Attention Relies on Dynamic Interactions between Prelimbic Cortex and Anterior Cingulate Cortex - Totah, Nelson K. B. (Oxford University Press, 2013)
An emerging view of prefrontal cortex (PFC) function is that multiple PFC areas process information in parallel, rather than as distinct modules. Two key functions assigned to the PFC are the regulation of top-down attention and stimulus-guided action. Electrophysiology and lesion studies indicate the involvement of both the anterior cingulate cortex (ACC) and prelimbic cortex (PL) in these functions. Little is known, however, about how these cortical regions interact. We recorded single unit spiking and local field potentials (LFPs) simultaneously in rodents during a sustained attention task and assessed interactions between the ACC and PL by measuring spike–LFP phase synchrony and LFP–LFP phase synchrony between these areas. We demonstrate that the magnitude of synchrony between the ACC and PL, before stimulus onset, predicts the subjects' behavioral choice after the stimulus. Furthermore, neurons switched from a state of beta synchrony during attention to a state of delta synchrony before the instrumental action. Our results indicate that multiple PFC areas interact during attention and that the same neurons may participate in segregated assemblies that support both attention and action.